MISUSE OF TOPICAL STEROIDS BY PATIENTS SEEKING DERMATOLOGY OPD - Kalyani , Parag Gopal (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: In dermatological offices nowadays, topical corticosteroids are the most often recommended drugs. Their anti-inflammatory, vasoconstrictive, anti-proliferative, and immunosuppressive characteristics mediate the clinical consequences. They are extremely effective medications used to treat a variety of inflammatory and autoimmune dermatological diseases. Off-label use of TC appears to be a prevalent clinical practice in India, according to information on recognized dermatological indications of TC published on the Central Drugs Standard Control Organization (CDSCO) website (although indications are not specified for all the TC molecules). Material and method: A tertiary care hospital’s Department of Dermatology outpatient clinic hosted a cross-sectional observational questionnaire-based study. A total of 170 individuals of all ages and genders who had used topical corticosteroids inappropriately (that is, for circumstances for which they are not advised) for specific skin issues and had displayed at least one adverse effect from these medications were recruited in a sequential manner. These comprised at least one of the following symptoms: plethoric face and telangiectasia, infantile gluteal granuloma, pyoderma, stretch marks, hyper/hypopigmentation, tinea incognito, facial acne, facial hypertrichosis, and cutaneous atrophy. Results: Most common adverse effect observed in present study was tinea incognito (34.71%) followed by aggravation of the lesion (21.76%). Other adverse effects observed were post-Inflammatory hypo/ hyper pigmentation (12.35%), plethoria/ telangiectasia (11.18%), atrophy/ striae (7.64%), facial acne (6.47%), photosensitivity (3.53%), and hypertrichosis (2.35%). Conclusion: The issue is made worse by the ease with which a patient can obtain these drugs, even without a valid prescription. In our study, it was discovered that younger age groups, particularly females, abused steroids more frequently. Steroid misuse is thus a widespread issue in India due to the ease with which topical steroids may be obtained, the difficulty patients have in seeing dermatologists, and a lack of awareness about non-adverse doctors. The results of our study’s data show that this issue is already serious, and immediate action should be done to address it by making steroids a prescription-only drug rather than an over-the-counter drug. Key Words: Topical Steroid, Corticosteroid, Acne, CDSCO and Adverse effect